Social support following diagnosis and treatment for colorectal cancer and associations with health‐related quality of life: Results from the UK ColoREctal Wellbeing (CREW) cohort study. Issue 12 (1st November 2017) - Haviland, Joanne; Sodergren, Samantha; Calman, Lynn; Corner, Jessica; Din, Amy; Fenlon, Deborah; Grimmett, Chloe; Richardson, Alison; Smith, Peter W.; Winter, Jane; ,; Foster, Claire
Abstract: Objective: Social support is acknowledged as important in cancer survivorship, but little is known about change in support after cancer diagnosis and factors associated with this, particularly in colorectal cancer. The CREW cohort study investigated social support up to 2 years following curative intent surgery for colorectal cancer. Methods: A total of 871 adults recruited pre‐treatment from 29 UK centres 2010 to 2012 consented to follow‐up. Questionnaires at baseline, 3, 9, 15, and 24 months post‐surgery included assessments of social support (Medical Outcomes Study‐Social Support Survey, MOS‐SSS) and health‐related quality of life (HRQoL). Socio‐demographic, clinical and treatment details were collected. Longitudinal analyses assessed social support over follow‐up, associations with participant characteristics, and HRQoL. Results: Around 20% were living alone and 30% without a partner. Perceived social support declined in around 29% of participants, with 8% of these reporting very low levels overall from baseline to 2 years (mean MOS‐SSS overall score < 40 on a scale from 0 to 100). Older age, female gender, greater neighbourhood deprivation, presence of co‐morbidities, and rectal cancer site were significantly associated with reductions in perceived support. Poorer HRQoL outcomes (generic health/QoL, reduced wellbeing, anxiety, and depression) were significantly associated with lower levels of social support. Conclusions: Levels of social support decline following colorectal cancer diagnosis and treatment in nearly a third of patients and are an important risk factor for recovery of HRQoL. Assessment of support early on and throughout follow‐up would enable targeted interventions to improve recovery, particularly in the more vulnerable patient groups at risk of poorer social support.